Effectiveness of interpersonal communication on patient satisfaction in goverment out patient clinics, in the district of Kuala Langat, Selangor , 1997 - Norhayati Rusli; Mohd Hatta Ramli (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study was carried out in the District of Kuala Langat, Selangor in February 1997. The intention is to determine the relationship between effective communication of individuals towards patient satisfaction and factors that influence effective communication. The study was carried out in outpatient clinics of six health clinics and a district hospital which involves 336 patients selected using universal sampling. The data was obtained using guided questionnaires. The outcome of the study shows significant relationship between effective communication and patient satisfaction (t = 3.06, p < 0.05). Communication media, verbal communication and non verbal communication are also the factors that shows significant relationship towards effective communication. Other factors studied such as patient age, sex and ethnic group, doctor's attitude, sex of the doctor and doctor's communication skill do not show any significant relationship towards effective communication. Multiple logistic regression analysis was carried out between media factor, verbal communication and non-verbal communication against effective communication. The result shows that a doctor using media during interaction with a patient, communicates 2.8 times more effective than a doctor who does not utilise the media. For a doctor using verbal communication with easily understood language, the communication is 3.4 times more effective than a doctor who does not use an easily understood language. Meanwhile, a doctor who use non-verbal communication, produce 2.3 times more effective communication as compared to a doctor who did otherwise. By controlling all the confounding factors at the same time, the three factors above still shows significant relationship. This indicates that the factors are the predictive factors towards effective communication. Since effective communication by doctors is an important factor in ensuring patient satisfaction, therefore a comprehensive study should be carried out by taking into consideration other factors which would contribute to effective communication and patient satisfaction